PROFIL PENDERITA TUMOR KELENJAR LIUR DI RSUP PROF. DR. R.D. KANDOU MANADO PERIODE JULI 2012-JUNI 2015 - Iman, Wirawan; Merung, Marselus; Aschorijanto, Ainun (Universitas Sam Ratulangi, 2016)
Abstract: Salivary glands tumours are relatively rare to find. There is still no adequate data about the incidence of salivary gland tumours in Indonesia. The main objective of this research was to cognise the profile of salivary glands tumours patients in Prof. Dr. R.D. Kandou Central General Hospital Manado from July 2012 to June 2015. Methods used is descriptive retrospective. The results showed there are 37 patients with salivary gland(s) tumour(s). Male was 59,5% and female was 40,5%. By age groups found that <19 years for 2.7%, 19-30 years for 8,2%, 31-45 years for 21.6%, 46-60 years for 37,8%, >60 years for 29,7%. Based on the histopathological classification, pleomorphic adenoma for 56.8%, Whartin's tumor for 8.1%, myoepithelioma for 2,7%, basal cell adenoma for 2.7%, oncocytoma for 2.7%, cystadenoma for 5.4%, canalicular adenoma for 2.7%, mucoepidermoid carcinoma for 10.8%, adenocarcinoma for 5.4%, and acinic cell carcinoma for 2.7%. Based on the location of the tumours’ appearance, parotid gland for 83.8%, submandibular gland for 13.5%, minor salivary glands for 2.7%. Based by the incidences annually, first year for 21.6%, second year for 32.3%, and the third year for 46.1%.Conclusion: Males are more than females, most commonly found in the age group of 51-60 years, the most commonly benign tumour found is the pleomorphic adenoma, the most commonly found malign tumour is mucoepidermoid carcinoma, the most commonly location of the tumours’ appearance is the parotid gland. The salivary glands tumours continued to increase during the last three years.Suggestion: Still necessary to do further research about salivary glands tumours.Keywords: salivary glands tumours, age, gender, histopathology, location, profileAbstrak : Tumor kelenjar liur adalah tumor yang relatif sedikit dijumpai ditemukan. Belum ditemukan data yang lengkap tentang kejadian tumor kelenjar liur di Indonesia. Tujuan utama dari penelitian ini adalah untuk mengetahui profil penderita tumor kelenjar liur di RSUP Prof. Dr. R.D. Kandou Manado periode Juli 2012-Juni 2015. Metode penelitian yang digunakan adalah deskriptif retrospektif. Hasil penelitian memperlihatkan terdapat 37 penderita tumor kelenjar liur. Laki-laki sebanyak 59,5% dan perempuan 40,5%. Kelompok usia <16 tahun sebanyak 2,7%, 16-30 tahun sebanyak 8,1%, 31-45 tahun sebanyak 21,6%, 46-60 tahun sebanyak 37,8%, >60 tahun sebanyak 29,7%. Berdasarkan klasifikasi histopatologi jenis pleomorphic adenoma sebanyak 56,8%, Whartin’s tumor sebanyak 8,2%, myoepithelioma sebanyak 2,7%, basal cell adenoma sebanyak 2,7%, oncocytoma sebanyak 2,7%, cystadenoma sebanyak 5,4%, canalicular adenoma sebanyak 2,7%, mucoepidermoid carcinoma sebanyak 10,8%, adenocarcinoma sebanyak 5,4%, acinic cell carcinoma sebanyak 2,7%. Berdasarkan lokasi munculnya tumor, kelenjar parotis sebanyak 83,8%, kelenjar submandibula sebanyak 13,5%, kelenjar liur minor sebanyak 2,7%. Berdasarkan jumlah pertahunnya, tahun pertama sebanyak 21,6%, tahun kedua sebanyak 32,3%, dan tahun ketiga sebanyak 46,1%.Kesimpulan : Penderita laki-laki lebih banyak daripada perempuan, paling banyak ditemukan pada kelompok usia 46-60 tahun, tumor jinak yang paling banyak ditemukan adalah pleomorphic adenoma, tumor ganas yang paling banyak ditemukan adalah mucoepidermoid carcinoma, lokasi tersering munculnya tumor adalah kelenjar parotis. Penderita tumor kelenjar liur terus meningkat selama tiga tahun terakhir.Saran : Perlu dilakukan penelitian lebih lanjut tentang tumor kelenjar liurKata Kunci : tumor kelenjar liur, usia, jenis kelamin, histopatologi, lokasi, profil